Chryseobacterium Indologenes–Associated Pneumonia in 2 Neonates. Issue 3 (March 2017) - Radera, Shruti; Tripathi, Shalini; Agarwal, Jyotsna; Kumar, Mala
Abstract : Chryseobacterium species are widely distributed in nature and can rarely cause human infection. Few cases reported in hospitalized patients are in immunocompromised hosts with indwelling devices and associated comorbidities. Chryseobacterium species are usually multidrug resistant. We describe 2 cases of Chryseobacterium indologenes– associated pneumonia in neonates and review the published infant cases.